Goethite (α‐FeOOH) photocatalytic activity at natural concentrations by the addition of H 2 O 2 at neutral pH and the simultaneous presence of fluoride and bicarbonate - Alvear Daza, John Jairo (2023)
The effect of the simultaneous presence of fluoride (0.15–1.2 mg L−1), bicarbonates (83.6–596 mg L−1), and synthesized goethite (0.3 mg L−1) at typical concentrations often found in groundwater samples was evaluated on the degradation of 2,4-dichlorophenoxyacetic acid (2,4-D) at pH 6.9 under simulated sunlight irradiation (300 W m−2) and H2O2 concentrations of 10 mg L−1. The 2,4-D removal was strongly enhanced by the presence of fluoride. F− could modify the surface of iron (hydr)oxide, leading to the formation of surface Fe–F bonds benefiting the formation of free •OH, producing upward band bending, reducing the electron-hole recombination, and enhancing the electron transfer to H2O2. On the other hand, bicarbonate may react with •OH generating CO3−• species that could participate in pollutant oxidation, while solar light-induced H2O2 photolysis also played an important role in removing 2,4-D. These findings suggest that tuning of iron (hydr)oxides by fluoride could take place in real groundwater, generating photocatalysts with a high activity that could participate, by adding H2O2, in the enhancement of sunlight photoinduced natural abiotic processes for pollutant abatement.